Implementasi model pembelajaran kooperatif tipe jigsaw sebagai upaya meningkatkan prestasi belajar memahami unsur intrinsik cerpen - I Nyoman Putra (Indonesian Journal of Educational Development, 2021)
This research is a classroom action research that aims to determine whether the Jigsaw cooperative learning model can improve student achievement. The research subjects were 35 students of SMA Negeri 1 Sukawati class XI MIPA2, odd semester academic year 2019/2020. The object of research is student achievement in the material of understanding the short story intrinsic elements. Collecting data in this study using learning achievement tests. While the data analysis used quantitative descriptive analysis. This research is said to be successful if the learning achievement classically reaches an average of at least 80 (equivalent to KKM). The results obtained from this study are the Jigsaw cooperative learning model can improve student achievement. This is evident from the results obtained in the first cycle an average learning achievement of 77.63, an increase of 6.45% from 72.69 in the initial activity value. In the second cycle the average learning achievement reached 82.71, an increase of 6.57% from the first cycle for learning achievement. The conclusion that can be obtained from this research is that the type of jigsaw cooperative learning model can improve student achievement in class XI MIPA2 SMA Negeri 1 Sukawati in Indonesian, especially in basic competence 7.2, namely explaining the intrinsic elements of short stories. Penelitian ini merupakan penelitian tindakan kelas bertujuan untuk mengetahui apakah model pembelajaran Kooperatif tipe Jigsaw dapat meningkatkan prestasi belajar siswa. Subjek penelitian adalah siswa SMA Negeri 1 Sukawati kelas XI MIPA2 berjumlah 35 orang siswa, semester ganjil tahun pelajaran 2019/2020. Objek penelitian adalah prestasi belajar siswa pada materi memahami unsur intrisik cerpen. Pengumpulan data dalam penelitian ini menggunakan tes prestasi belajar. Sedangkan analisis datanya menggunakan analisis deskriptif kuantitatif. Penelitian ini dikatakan berhasil apabila prestasi belajar secara klasikal mencapai rata-rata minimal 80 (setara dengan KKM). Hasil yang diperoleh dari penelitian ini adalah model pembelajaran Kooperatif tipe Jigsaw dapat meningkatkan prestasi belajar siswa. Ini terbukti dari hasil yang diperoleh pada siklus I rata-rata prestasi belajar 77,63 meningkat 6,45% dari 72,69 pada nilai kegiatan awal. Pada siklus II rata-rata prestasi belajar mencapai 82,71 meningkat 6,57% dari siklus I untuk prestasi belajar. Kesimpulan yang dapat diperoleh dari penelitian ini adalah model pembelajaran kooperatif tipe jigsaw dapat meningkatkan prestasi belajar siswa kelas XI MIPA2 SMA Negeri 1 Sukawati pada bahasa Indonesia khususnya pada kompetensi dasar 7.2 yaitu menjelaskan unsur-unsur intrinsik cerpen.